2018
DOI: 10.3389/fpsyg.2017.02304
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Gratification, Delay Discounting and their Associations with Age, Episodic Future Thinking, and Future Time Perspective

Abstract: The delay of gratification (DoG) in children is widely investigated with an experimental procedure originally called the “marshmallow test,” whereas the studies on self-regulation (SR) in adolescents and adults usually use self-report questionnaires. Delay discounting (DD) measures simplify the DoG procedure and focus on monetary rewards. The aim of this study was to investigate age differences in DoG and DD from childhood to old age using a test that is suitable for both children and adults. Furthermore, inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 81 publications
2
32
0
Order By: Relevance
“…Indeed, among those who produced systematic data on the DD task, 78% delayed on at least three of the four DoG trials, meaning there was relatively little variance in the DoG data. It is possible that a more sensitive DoG task would yield a relation with DD (see Göllner et al, 2018), although we note that the DoG task was sufficiently sensitive to yield a significant zero-order correlation with sensation seeking. As things stand, though, despite research with adults suggesting that delayed reward tasks involving hypothetical rewards essentially measure something similar to those involving real rewards (Madden, Begotka, Raiff, & Kastern, 2003), we cannot yet be confident that this is the case in children.…”
Section: Relations With Other Measuresmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, among those who produced systematic data on the DD task, 78% delayed on at least three of the four DoG trials, meaning there was relatively little variance in the DoG data. It is possible that a more sensitive DoG task would yield a relation with DD (see Göllner et al, 2018), although we note that the DoG task was sufficiently sensitive to yield a significant zero-order correlation with sensation seeking. As things stand, though, despite research with adults suggesting that delayed reward tasks involving hypothetical rewards essentially measure something similar to those involving real rewards (Madden, Begotka, Raiff, & Kastern, 2003), we cannot yet be confident that this is the case in children.…”
Section: Relations With Other Measuresmentioning
confidence: 83%
“…Finally, we turn to the lack of a relation between the DD and DoG measures. Relatively few previous studies, with any age group, have included both these measures (though see Göllner, Ballhausen, Kliegel, & Forstmeier, ). In a recent meta‐analysis of the convergent validity of measures of self‐control, Duckworth and Kern () report an average across‐task correlation of r = .21 from studies that used at least two DoG tasks (although this was based on a sample of just four papers, indicative of the small number of studies that have reported correlations among different DoG measures).…”
Section: Discussionmentioning
confidence: 99%
“…According to Göllner, Ballhausen, Kliegel, and Forstmeier's research, people with a strong future orientation and without past orientation were the best in the delay of gratification, followed by people in the time expansive category with both future and past orientation. 29 Bembenutty and Karabenick also suggested that a time perspective that is future-oriented or at least considers both past and future could improve the ability to delay gratification. 15 However, these results have not been replicated by rigorous studies and no research has explored the mechanism of the relationship, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…27 On the other hand, individuals with long-term time perception have longer-term plans for the future and exhibit more successful delay of gratification. 28,29 Researches showed higher futureoriented TP predict less addictive behaviors and healthier behaviors. 12,30 However, there is no known mechanism by which the TP affects the delay of gratification so far although the relationship between TP and the delay of gratification has been widely researched.…”
Section: Introductionmentioning
confidence: 99%
“…We set the upper age limit at 63 years to limit the potential confounding effect of older age. Older adults may show a greater preference for immediate over delayed rewards [35], and this preference may be stronger among older adults with mild cognitive impairment [36-38] and Alzheimer disease [37,38]. On the other hand, other studies indicate that older adults may show a greater preference for delayed rewards compared with middle-aged adults [36].…”
Section: Methodsmentioning
confidence: 99%